IMITATING MODELLING OF ADVERTISING CAMPAIGN ON THE BASIS OF MODEL OF DIFFUSION OF BASS - Inessa Penkova; Alina Bodnar; Elena Iskra (Вестник Северо-Кавказского федерального университета)
The article aims at creating the simulating model for managing the company's advertising budget. This model is developed using the AnyLogic simulation tool. It is based on the Bass diffusion model, which assumes active usage of communication channels between participants connected. Therefore, the key points of the model are the dependence ofprofit and sales volumes, under the conditions of «inclusion» and «deactivation» of the cost to advertise goods, on the one hand, and the consumers' opinions influencing the decision of potential buyers, on the other hand.